DEVELOPMENT OF AN ACEHNESE CULTURE-BASED TEACHING MODULE TO ENHANCE ELEMENTARY STUDENTS’ UNDERSTANDING OF MATHEMATICAL CONCEPTS IN ACEH BESAR - Tria Marvida; Sofiyan Siregar; Helminsyah Helminsyah (PIONIR: JURNAL PENDIDIKAN, 2025)
Mathematics learning in elementary schools is often considered abstract and difficult for students to understand due to the lack of connection with cultural contexts and everyday life. Studies show that most students in Aceh Besar experience difficulties in understanding mathematical concepts, particularly in abstract topics such as fractions and geometry. This is caused by conventional teaching methods, the limited availability of contextual teaching materials, and the lack of integration of local culture as a learning medium. This study aims to develop an Acehnese culture-based teaching module that is valid, practical, and effective in improving elementary school students’ conceptual understanding of mathematics in Aceh Besar. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 118 fourth-grade students from three schools (SDN 1 Peukan Bada, SDN 2 Peukan Bada, and SDN Lamteh) along with three classroom teachers. The instruments used included validation sheets from subject matter, media, and cultural experts, interview guidelines for the module practicality test, and conceptual understanding tests. Data were analyzed using a mixed-methods approach with an Explanatory Sequential design, in which quantitative analysis was followed by qualitative analysis. The results showed that the Acehnese culture-based teaching module was judged valid by experts, practical for teachers to use, and effective in improving students’ mathematical conceptual understanding. This was indicated by the significant increase in average pretest to posttest scores, N-gain values in the high category, paired t-test and Wilcoxon results with p < 0.001, as well as a very large effect size. Therefore, the Acehnese culture-based teaching module is feasible to be used as an alternative teaching material in elementary school mathematics learning. Keywords: Teaching module development, Acehnese culture, Conceptual understanding, Mathematics, Elementary school